Sex-Based Differences in Human Immunodeficiency Virus Type 1 Reservoir Activity and Residual Immune Activation. (29th October 2018) - Scully, Eileen P; Gandhi, Monica; Johnston, Rowena; Hoh, Rebecca; Lockhart, Ainsley; Dobrowolski, Curtis; Pagliuzza, Amélie; Milush, Jeffrey M; Baker, Christopher A; Girling, Valerie; Ellefson, Arlvin; Gorelick, Robert; et al.
Abstract: Plasma human immunodeficiency virus type 1 (HIV-1) RNA levels in women are lower early in untreated HIV-1 infection compared with those in men, but women have higher T-cell activation and faster disease progression when adjusted for viral load. It is not known whether these sex differences persist during effective antiretroviral therapy (ART), or whether they would be relevant for the evaluation and implementation of HIV-1 cure strategies. We prospectively enrolled a cohort of reproductive-aged women and matched men on suppressive ART and measured markers of HIV-1 persistence, residual virus activity, and immune activation. The frequency of CD4 + T cells harboring HIV-1 DNA was comparable between the sexes, but there was higher cell-associated HIV-1 RNA, higher plasma HIV-1 (single copy assay), and higher T-cell activation and PD-1 expression in men compared with women. These sex-related differences in immune phenotype and HIV-1 persistence on ART have significant implications for the design and measurement of curative interventions.